2014
DOI: 10.1007/s10493-014-9851-6
|View full text |Cite
|
Sign up to set email alerts
|

Ticks and rickettsial infection in the wildlife of two regions of the Brazilian Amazon

Abstract: During 2009-2012, wild animals and their ticks were sampled in two areas within the Amazon biome of Brazil, in the states of Mato Grosso and Pará. Animal tissues, blood, and ticks were molecularly tested for Rickettsia and Coxiella DNA. A total of 182 wild animals were sampled, comprising 28 mammalian, five avian, and three reptilian species. Animal tissues or blood were all negative for Rickettsia or Coxiella DNA. A total of 454 ticks (22 larvae, 226 nymphs, 127 males, 79 females) were collected from 52 (28.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
45
0
8

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(61 citation statements)
references
References 45 publications
8
45
0
8
Order By: Relevance
“…In the present study, adults of A. goeldii and A. nodosum were identified on T. tetradactyla, corroborating MARTINS et al (2014, 2015a) and SOARES et al (2015, who also identified southern tamanduas as hosts for these two species of ixodids in the North region of the country.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…In the present study, adults of A. goeldii and A. nodosum were identified on T. tetradactyla, corroborating MARTINS et al (2014, 2015a) and SOARES et al (2015, who also identified southern tamanduas as hosts for these two species of ixodids in the North region of the country.…”
Section: Resultssupporting
confidence: 89%
“…The ticks Amblyomma goeldii and Amblyomma nodosum have also been described as parasitizing southern tamanduas during the adult stage (MARTINS et al, 2014(MARTINS et al, , 2015aSOARES et al, 2015). In the present study, adults of A. goeldii and A. nodosum were identified on T. tetradactyla, corroborating MARTINS et al (2014, 2015a) and SOARES et al (2015, who also identified southern tamanduas as hosts for these two species of ixodids in the North region of the country.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…As bactérias Rickettsia rickettsii, R. parkeri, Rickettsia sp. cepa Mata Atlântica são consideradas importantes zoonoses (Soares et al 2015, Oliveira et al 2017, bem como o Anaplasma phagocytophilum, Ehrlichia chaffeensis e E. ewingii (Vieira et al 2011).…”
Section: Introductionunclassified
“…Ela pode representar uma valiosa fonte de informações, principalmente em localidades nunca antes estudadas, pois funciona como indicadora da qualidade do ambiente ao demonstrar, para agentes que hospeda, os desequilíbrios a que está exposta. Fato este pode sugerir boa capacidade de suporte e qualidade ambiental quando suas espécies sobrevivem bem (Thompson et al 2009, Soares et al 2015.…”
Section: Introductionunclassified